Single-Cut Single-Screw Capitate-Shortening Osteotomy for Kienbock's Disease - Bain, Gregory I.; Krishna, Sathya Vamsi; MacLean, Simon Bruce Murdoch; Agrawal, Parth (Journal of Wrist Surgery, 2020)
Background Kienbock's disease, in spite of an uncertain natural history, is known to cause lunate compromise, leading to central column collapse, carpal instability, and degenerative arthritis of the wrist. Joint leveling procedures are performed in the early stages of Kienbock's disease to “unload” the lunate. Capitate shortening is the preferred procedure in Kienbock's patients with positive ulnar variance.Description of Technique We describe the rationale and a simplified technique of capitate shortening in early Kienbock's disease. This is a single-cut osteotomy with single-screw stabilization.Patients and Methods We have performed this technique in three cases. We present a case of a 26-year-old male who presented with a 1-year history of pain in his right wrist. Radiology performed demonstrated lunate sclerosis. Diagnostic arthroscopy revealed healthy articular surfaces. Single osteotomy capitate shortening was performed with an oscillating saw and fixed with a single cannulated compression screw. A shortening of 1.5mm was obtained with this technique.Results At 1- to 2-year follow-up, all three patients had considerable pain relief but did not have a complete resolution of pain. There was a significant improvement in function and grip strength. There have been no cases with infection, nonunion, avascular necrosis or a need for a salvage procedure.Conclusion The simplified technique of capitate shortening is easy to perform, less traumatic to the capitate vascularity, and leads to good short-term functional results.
Keywords: Kienbock's disease; capitate shortening; joint leveling; capitate vascularity; capitate osteotomy